2007
DOI: 10.1111/j.1460-9568.2007.05371.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrosplenial and hippocampal brain regions in human navigation: complementary functional contributions to the formation and use of cognitive maps

Abstract: The ability to orientate within familiar environments relies on the formation and use of a mental representation of the environment, namely a cognitive map. Neuropsychological and neuroimaging studies suggest that the retrosplenial and hippocampal brain regions are involved in topographical orientation. We combined functional magnetic resonance imaging with a virtual-reality paradigm to investigate the functional interaction of the hippocampus and retrosplenial cortex during the formation and utilization of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
204
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(219 citation statements)
references
References 60 publications
11
204
4
Order By: Relevance
“…Lastly, our finding of smaller increases in the low frequency activity during recall as compared to acquisition together with more alpha activity during the latter may be explained by the use of the anterior FO electrodes. Such an assumption would be compatible with findings coming from an fMRI study (Iaria et al 2007) which revealed complementary roles of the anterior and posterior hippocampus in navigation with the former being involved in the formation of a cognitive map while the latter in using it.…”
Section: Discussionsupporting
confidence: 87%
“…Lastly, our finding of smaller increases in the low frequency activity during recall as compared to acquisition together with more alpha activity during the latter may be explained by the use of the anterior FO electrodes. Such an assumption would be compatible with findings coming from an fMRI study (Iaria et al 2007) which revealed complementary roles of the anterior and posterior hippocampus in navigation with the former being involved in the formation of a cognitive map while the latter in using it.…”
Section: Discussionsupporting
confidence: 87%
“…Correspondingly, the pattern of activation in the training trials (bilateral hippocampus, medial prefrontal, and caudate) overlaps with both the allocentric and the sequential egocentric activations during probe trials. Activations that distinguished allocentric from sequential egocentric strategies included the bilateral parietooccipital sulcus: a region previously shown to be related to allocentric spatial processing (22,25,50), retrieval of spatial memories into imagery (24), and navigation (15,51). The reverse pattern (sequential egocentric vs. allocentric strategies) shows activations of the posterior insula, which corresponds to the human analog of the primate vestibular cortex (52) and posterior parietal operculum, which might be related to movement processing (53).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that the parahippocampus is involved in recognition of scenes, even when these are lacking any landmarks (12,(14)(15)(16)(17). The hippocampus and parahippocampus may fulfill different roles in spatial navigation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the hippocampus for navigation in large-scale environments has been amply demonstrated in both animal (6-8) and human studies (9-11). Besides the hippocampus, several other areas in the posterior mesial lobe and posterior parietal, occipital, and infero-temporal cortices also play an important role in navigation (9,(12)(13)(14)(15)(16)(17).The neural correlates of navigation in congenital blindness remain elusive, in part owing to the difficulty in testing navigational skills of blind subjects within the setting of a functional brain imaging study. To circumvent this difficulty, we trained blind and sighted subjects in a spatial navigation task using the tongue display unit (TDU), a visual-to-tactile sensory substitution device that converts visual information into electro-tactile pulses applied to the tongue (18, 19).…”
mentioning
confidence: 99%
See 1 more Smart Citation